High Efficiency Control of Internal Combustion Engines in Blended Charge Depletion/Charge Sustenance Strategies for Plug-in Hybrid Electric Vehicles - Overington, Shane; Rajakaruna, Sumedha (Institute of Electrical and Electronics Engineers, 2014)
This paper realizes a novel control strategy for the fuel consumption reduction in plug-in hybrid and hybrid electric vehicles having an internal combustion engine (ICE) and one or more motor/generators. The proposed control strategy combines power balancing and variable speed control to achieve a more efficient utilization of fossil fuel energy that is consumed over standardized drive cycles. Furthermore, a high-efficiency region in the ICE performance map is utilized to aid with energy management decisions. For the test bench, three vehicle models have been developed in ADVISOR (the software package utilized in this paper) using available measured data. After verifying the accuracy of models, the proposed control strategy is implemented in the three vehicles to demonstrate reduced fuel consumption. The proposed control strategy is applicable to parallel-connected and power-split-connected topologies.